2020
DOI: 10.1002/mrm.28252
|View full text |Cite
|
Sign up to set email alerts
|

Influence of labeling parameters and respiratory motion on velocity‐selective arterial spin labeling for renal perfusion imaging

Abstract: Purpose Arterial transit time uncertainties and challenges during planning are potential issues for renal perfusion measurement using spatially selective arterial spin labeling techniques. To mitigate these potential issues, a spatially non‐selective technique, such as velocity‐selective arterial spin labeling (VSASL), could be an alternative. This article explores the influence of VSASL sequence parameters and respiratory induced motion on VS‐label generation. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 10 publications
(50 citation statements)
references
References 38 publications
1
49
0
Order By: Relevance
“…First of all, during the paced-breathing condition subjects were asked to shortly hold their breath during the image acquisition, but not necessarily during labeling. However, effects are expected to be small because a cut-off velocity (5 cm/s) was chosen to prevent subtraction artefacts because of respiratory motion, and our results indeed did not show the typical high intensity subtraction artefacts as described by Bones et al 5 In addition, VSASL-and AccASL-labeling have been shown to depend on the cardiac cycle. 36 Effects are expected to average out when using a sufficient number of averages, but will still lower tSNR-values.…”
supporting
confidence: 65%
See 4 more Smart Citations
“…First of all, during the paced-breathing condition subjects were asked to shortly hold their breath during the image acquisition, but not necessarily during labeling. However, effects are expected to be small because a cut-off velocity (5 cm/s) was chosen to prevent subtraction artefacts because of respiratory motion, and our results indeed did not show the typical high intensity subtraction artefacts as described by Bones et al 5 In addition, VSASL-and AccASL-labeling have been shown to depend on the cardiac cycle. 36 Effects are expected to average out when using a sufficient number of averages, but will still lower tSNR-values.…”
supporting
confidence: 65%
“…Image acquisition was planned in coronal–oblique orientation, parallel to the muscles anterior to the kidney, to minimize through‐slice motion. Optimal scan parameters for renal imaging were not known for all flow‐based ASL techniques, so they were chosen partly based on previous research 5,23,24 and partly on preliminary experiments (Table 1). The durations of the VSS‐ and ASS‐labeling modules were set to 50 ms, and gradient orientation to the slice direction, that is, anterior–posterior (AP) direction, to minimize effects of respiratory motion on labeling 5 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations